A Stk4-Foxp3-NF-κB p65 transcriptional complex promotes Treg cell activation and homeostasis - BARIŞ, SAFA (My University, 2022)
The molecular programs involved in regulatory T (Treg) cell activation and homeostasis remain incompletely understood. Here, we show that T cell receptor (TCR) signaling in Treg cells induces the nuclear translocation of serine/threonine kinase 4 (Stk4), leading to the formation of an Stk4-NF-κB p65-Foxp3 complex that regulates Foxp3- and p65-dependent transcriptional programs. This complex was stabilized by Stk4-dependent phosphorylation of Foxp3 on serine-418. Stk4 deficiency in Treg cells, either alone or in combination with its homolog Stk3, precipitated a fatal autoimmune lymphoproliferative disease in mice characterized by decreased Treg cell p65 expression and nuclear translocation, impaired NF-κB p65-Foxp3 complex formation, and defective Treg cell activation. In an adoptive immunotherapy model, overexpression of p65 or the phosphomimetic Foxp3S418E in Stk3/4-deficient Treg cells ameliorated their immune regulatory defects. Our studies identify Stk4 as an essential TCR-responsive regulator of p65-Foxp3-dependent transcription that promotes Treg cell-mediated immune tolerance.
Keywords: Tıp; Yaşam Bilimleri; Sağlık Bilimleri; Temel Bilimler; Medicine; Life Sciences; Health Sciences; Natural Sciences; Klinik Tıp (MED); Yaşam Bilimleri (LIFE); Klinik Tıp; İmmünoloji; ALERJİ; Clinical Medicine (MED); Life Sciences (LIFE); CLINICAL MEDICINE; IMMUNOLOGY; ALLERGY; İmmünoloji ve Alerji; Immunology and Allergy; Immunology